TECHNICAL AND VOCATIONAL EDUCATION AND TRAINING (TVET) AND APPRENTICESHIP PRACTICE IN NIGERIA: PROBLEMS AND PROSPECTS - Danyaro, Kankia Jamilu; Awang, Halizah (Online Journal for TVET Practitioners, 2018)
It has been observed that the rekindling of the values of apprenticeship has been one of the most significant trends in Technical and Vocational Education and Training (TVET) in recent years, by organizing the youths to undergo apprenticeship training in various vocational fields which could make them independent on the completion of such skill acquisitions but, this is usually faced with multiple of problems. This paper intends to review the inception of apprenticeship practice and Technical and Vocational Education (TVET) in Nigeria. It expounded on the Development of Technical and Vocational Education and Training (TVET) after independence and the role of technical and vocational education in nation building. Problems and prospect were outlined to suggest way forward in line with the global needs for sustainable self-employment strategies especially among the youths.